BBU-RRH switching schemes for centralized RAN - Namba, S.; Warabino, T.; Kaneko, S. (2012 7th International ICST Conference on Communications and Networking in China, 2012)
Mobile data traffic has been increasing at a rapid pace over the past few years due to the rise of both smartphones and tablets. Small cell deployments are one of the most effective ways to increase system capacity by improving the spatial reuse of radio resources for the explosive increase in traffic loads. However, it leads to be a large cost impact for operators. Centralized RAN (C-RAN) has been proposed, which has the potential ability to reduce network costs due to reductions in civil work and/or electricity costs at local base station sites by centralizing baseband units to the center side. Moreover, C-RAN can be expected to further reduce network costs using baseband unit (BBU) pooling functions in which the centralized BBU resources can be dynamically allocated to remote radio heads (RRHs) depending on traffic load. This paper proposes semi-static and adaptive BBU-RRH switching schemes for C-RAN and evaluates their effectiveness through simulations. Under conditions of 100 RRHs, here, a RRH is comparable to a cell, and traffic distribution with a typical traffic profile in office (business) area, we confirmed that the number of BBUs can be reduced by 26% and 47% for semi-static and adaptive schemes, respectively, compared with conventional cell deployment.